Cognitive dysfunction in chronic Chagas disease cardiomyopathy - Jesângeli Sousa Dias; Amanda M. Lacerda; Rodrigo M. Vieira-de-Melo; Leila C. Viana; Pedro A.P. Jesus; Francisco J.F.B. Reis; Ricardo Nitrini; Helenice Charchat-Fichman; Antônio A. Lopes; Jamary Oliveira-Filho (Dementia & Neuropsychologia)
Abstract Chagas disease (CD) remains a major cause of stroke in developing countries, but cognitive repercussion of CD has not been well studied. Objective: To compare the frequency and pattern of cognitive dysfunction in patients with CD cardiomyopathy (CDC) and other cardiomyopathies (OC). Methods: We studied 37 patients with CDC and 42 patients with OC with similar age, educational level and cardiac systolic function. Cognitive tests were applied to both groups by a single examiner blinded to CD status. Logistic regression multivariable models were constructed to ascertain predictors of cognitive dysfunction for each test. Results: Cognitive dysfunction was detected in 9 (24%) CDC patients and 6 (14%) OC patients by Mini Mental State Exam (MMSE) corrected for educational level. Independent predictors of abnormal MMSE (p <0.05) included stroke history (OR=5.51; 95% CI=1.27-24.01) and digoxin use (OR=0.23, 95% CI=0.06-0.89), while CD showed a trend toward statistical significance (OR=4.63; 95% CI=0.87-24.73, p =0.07). Delayed recall of Rey's Complex Figure Test was significantly worse in CD patients, where this remained a significant predictor in the multivariable analysis (OR=4.67; 95% CI=1.23-17.68). Conclusions: Cognitive dysfunction is frequent in Chagas disease and should be considered as an outcome measure in Chagas disease studies.